2016
DOI: 10.1039/c6sc01272h
|View full text |Cite
|
Sign up to set email alerts
|

The rational design of specific SOD1 inhibitors via copper coordination and their application in ROS signaling research

Abstract: Based on the active site structure and catalytic mechanism of SOD1, we developed a new type of efficient and specific SOD1 inhibitor which can directly change the intracellular levels of H2O2 and O2˙–.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 64 publications
2
42
0
Order By: Relevance
“…CQ appears to coordinate Cu(II) with moderate affinity (55), and BPS has only been characterized as an Fe(II) chelator but is predicted to form a bis complex with Cu(II) (59). Physical interactions between the chemical compound and the SOD5 protein are likely to play key roles in dictating inhibitor efficacy as well as chelator metal affinities, as has been reported for chemical inhibitors of Cu,Zn-SOD1 (65).…”
Section: Metal Chelators As Chemical Inhibitors Of Copper-only Sod5mentioning
confidence: 85%
“…CQ appears to coordinate Cu(II) with moderate affinity (55), and BPS has only been characterized as an Fe(II) chelator but is predicted to form a bis complex with Cu(II) (59). Physical interactions between the chemical compound and the SOD5 protein are likely to play key roles in dictating inhibitor efficacy as well as chelator metal affinities, as has been reported for chemical inhibitors of Cu,Zn-SOD1 (65).…”
Section: Metal Chelators As Chemical Inhibitors Of Copper-only Sod5mentioning
confidence: 85%
“…58 Production and enhancement of ROS generation under high-energy radiation is an important factor in cancer radiotherapy. 59 Dihydroethidium (DHE) is a fluorescence probe used to detect the intracellular superoxide anion (O 2 − ), which is the initiator of the free radical chain reaction. Upon receiving highenergy X-ray radiation, high-Z NPs can enhance the O 2 − conversion to generate O 2 − .…”
Section: Activation Of Ros-mediated Signaling Pathwaysmentioning
confidence: 99%
“…To thoroughly understand the effects of the specific SOD1 inhibition with the inhibitor LD100 (Figure 1(a)) on the expression of the global proteome in the cancer cell, we first performed the global mRNA sequencing on the HeLa cells treated with and without 50 μ M LD100, and SOD1 activity was validated to be reduced by approximate 85% by this inhibitor [44]. The SOD1 knockdown group was set for comparison, and both the expression and protein levels of SOD1 were validated to be reduced by >80% in the SOD1 siRNA-treated HeLa cells after interference for 24 h relative to control (Figures S1(a) and S1(b)).…”
Section: Resultsmentioning
confidence: 99%
“…After mapping the reads of all mRNA sequencing samples in HeLa cells to the reference genome (Table S1), the total of 4513 differentially expressed genes (DEGs) was identified in the knockdown group and the total of 2650 DEGs was identified in the SOD1 inhibition group compared to the control group (Figure 1(b) and Figure S1(f)). The DEGs in the SOD1 knockdown group were much more than those in the SOD1 inhibition group, as SOD1 had been proposed to act as a nuclear transcription factor [26] and its specific inhibition altered only the intracellular ROS levels [44] and might not alter its activity as a nuclear transcription factor. However, 1145 overlapped DEGs in these two groups indicated that the expression of these genes was mainly regulated by the alterations of ROS levels resulted from the reduction of SOD1 activity (Figure 1(c)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation